Provincial Effects on Reading Achievement - Ma, Xin; Crocker, Robert (Alberta Journal of Educational Research, 2007)
Although Canadian students performed well on the 2000 Programme for International Student Assessment (PISA), there were considerable differences among provinces. Based on the Canadian sample of PISA 2000, our multilevel analysis examined the extent to which schools in various provinces produced differential effects on the reading achievement of their students. School characteristics that showed significant provincial effects on reading achievement included variables that described school context, school resources, and school climate, with most of these significant school-level variables being measures of school climate. Disciplinary climate and sense of belonging to school were the most important of significant school characteristics. They showed significant average effects by province on reading achievement, and their effects varied significantly across provinces. Results of our analysis suggest that provinces can use school effects to promote the reading achievement of their students.